Analisis Butir Soal Matematika Ulangan Akhir Semester Gasal Kelas VII Tahun 2016/2017 Berdasarkan Taksonomi TIMSS di SMP Kabupaten Sukoharjo - Arminia, Aisyah; , Prof. Dr. Budi Murtiyasa, M.Kom (2017)
This study aimed to analysis the item UAS odd mathematic class VII SMP in Kabupaten Sukoharjo year 2016/2017 in terms of domain content and domain cognitive taxonomy based on TIMSS 2015 Assessment Framework. Domain content consists of 30% Number, 30% of Algebra, Geometry 20%, and 20% Data and Chance. While the domain cognitive consists of 35% Knowledge, 40% Application, and 25% Reasoning. The method used is a qualitative deskripsif using interactive methods of data analysis techniques. The validity of the data in this study using triangulation investigator. The results of this study on the content of the domain, among others 47.5% Number, 52.5% of Algebra, Geometry 0%, and 0% Data and Chance. While the results of the domain cognitive include Knowledge 47.5%, 42.5% Implementation, and 10% Reasoning. These results are explained in terms of content and cognitive domain UAS matter is not in accordance with the taxonomy of the TIMSS 2015 Assessment Framework.